Pengaruh Latihan Gerak Aktif Menggenggam Bola Terhadap Kekuatan Otot Ekstremitas Atas Pada Pasien Stroke Iskemia di BRSU Tabanan - Indra Diputra, I Gusti Putu Agus (Coping: Community of Publishing in Nursing; Vol 2 No 1 (2014): JURNAL EDISI JANUARI-APRIL 2014, 2014)
Stroke is deficit neurologic syndrome that caused by cerebral vascular disease. Stroke can cause deficit of hand function. Objective of  study  to know effect of ball handgrip active exercise program to muscle power of upper extremity on stroke ischemic patients. Design of study is quasi experiment with  pre and post test one group design. Study was done at Public Hospital of Tabanan Regency on April until Mei 2013 with 30 samples of stroke ischemic patients after seventh day care was selected by using purposive sampling method. The ball handgrip active exercise program as long as one mount as experiment. Force of handgrip was measured by using handgrip dynamometer. The result of study showed mean of force of handgrip before exercise 31.77 Kg, after exercise 42.03 Kg. There was significant different of  mean of muscle power before and after exercise (p = 0.000). Conclusion of study there was significant affect of the ball handgrip active exercise program to muscle power of upper extremity on stroke ischemic patients. Recommended for the nurses to provide ball handgrip active exercise program to improve muscle power of upper extremity on stroke ischemic patients.
Keywords: Stroke ischemic, Handgrip, Exercise program